(untitled) (REMUNOM, 2023)
The importance of the legal business is becoming more and more Christian in the field of procedural law, mainly because it allows the parties involved in a judicial process to have autonomy to define certain rules and procedures. This type of business contributes to the efficiency, evolution and speed of the process, promoting cooperation between the parties. However, it is essential to respect the limits imposed by fundamental constitutional principles, such as due process of law, adversarial proceedings and full defense. What stands out as the core of the discussion is the admissibility of the use of procedural legal business in the waiver of the right of defense in debt confession.